Pluripotency genes of mammals: a network at work - Cancedda, Ranieri; Mastrogiacomo, Maddalena (Frontiers in Bioengineering and Biotechnology, 2025)
Pluripotency, i.e., the ability to differentiate into cells of all three germ layers, is a transient state of early embryonic cells. In mammals, during progression from pre-implantation to post-implantation stage, pluripotent cells undergo different state transitions characterized by changes in gene expression and development potential. These developmental states include: (i) a naive pluripotency (pre-implantation embryonic stem cells, or ESCs), (ii) an intermediate condition (formative state), and (iii) a primed pluripotency (late post-implantation ESCs derived from epiblasts also named EpiSCs). The transitions are regulated by an interconnected network of pluripotency-related genes. Transcription of genes such as Oct4, Sox2, and Nanog is crucial for obtaining and maintaining pluripotency. These three factors form an autoregulatory loop by binding to each other’s promoters to activate their transcription. Other factors play a significant ancillary role in the transcription factor network preserving cell pluripotency. In the review, we will also mention some of the more relevant cytokines, molecules, signaling pathways, and epigenetic modifications that induce and control pluripotency gene expression. The main goal of this review is to bridge the gap between the fields of genetics and stem cell biology and to set the ground for the application of this knowledge to the development of strategies and drugs to be used in a clinical environment.